2013
DOI: 10.3945/an.112.003160
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Frontiers of Population Nutrition Research: New Questions, New Methods, and New Approaches

Abstract: Nutrition research, ranging from molecular to population levels and all points along this spectrum, is exploring new frontiers as new technologies and societal changes create new possibilities and demands. This paper defines a set of frontiers at the population level that are being created by the increased societal recognition of the importance of nutrition; its connection to urgent health, social, and environmental problems; and the need for effective and sustainable solutions at the population level. The fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 214 publications
2
46
0
1
Order By: Relevance
“…Nutrition researchers1020212223 and organisations such as Cochrane11 are calling for reform of conventional evidence synthesis and translation approaches so they are better able to overcome limitations in available evidence and include evidence relevant to modern nutrition problems. Below we give two examples of reforms in public health.…”
Section: Skewed Evidencementioning
confidence: 99%
“…Nutrition researchers1020212223 and organisations such as Cochrane11 are calling for reform of conventional evidence synthesis and translation approaches so they are better able to overcome limitations in available evidence and include evidence relevant to modern nutrition problems. Below we give two examples of reforms in public health.…”
Section: Skewed Evidencementioning
confidence: 99%
“…This emphasis is not unique to the U.S. and similar initiatives exist in the United Kingdom, Canada, Australia and other countries (Bero et al, 1998; Brownson, Colditz, & Proctor, 2012). Developing effective approaches to EBP implementation is an important initiative for improving health care and social services globally and locally (Pelletier, Porter, Aarons, Wuehler, & Neufeld, 2013). …”
mentioning
confidence: 99%
“…For example, in an evaluation of nutrition surveillance in Botswana it was reported that some of the district-and clinic-level health staff had never seen a report from the system ( [117], p.4); similar observations were made in an evaluation of the Malawi INFSS system ( Table 1). The lack of involvement of stakeholders at lower levels and the need to increase their participation is often mentioned in the literature (for example, [42,[118][119][120]). The justification partly relates to the quality and use of data, which are linked: if those who collect data then use the resulting information, there should be more incentive for them to collect high quality data.…”
Section: Lack Of Participationmentioning
confidence: 99%